Amantadine reduces persistent fatigue during post-acute withdrawal phase in methamphetamine abstained individuals: A randomized placebo-controlled trial. (2nd November 2018) - Modarresi, Atieh; Eslami, Kaveh; Kouti, Leila; Hassanvand, Reza; Javadi, Mohammadreza; Sayyah, Mehdi
ABSTRACT: Background: Persistent fatigue is a common symptom of methamphetamine withdrawal. It disrupts the individual's social and professional lives as well as increasing the risk of relapse. This study aimed to assess the effects of amantadine in the treatment of persistent fatigue in methamphetamine-abstained individuals.Methods: A double-blind, placebo-controlled trial was conducted on 42 methamphetamine-abstained individuals who sought treatment for persistent fatigue. Participants were randomly assigned to two groups, receiving either amantadine 100 mg/day or placebo for 4 weeks. Treatment response was evaluated using Fatigue Severity Scale (FSS) and Chalder Fatigue Scale (CFS), recorded at the beginning and end of trial.Results: A substantial reduction in both fatigue scales was found in the amantadine group, while there was no significant change in the placebo group. Fatigue reduction in the amantadine and placebo groups was, respectively, 28% versus 6% ( p < 0.001) using the FSS and 24.3% and 4.5% ( p < 0.001) using the CFS. In addition, both scales showed that the rate of fatigue recovery was significantly higher in the amantadine versus placebo group ( p < 0.05).Conclusions: Persistent fatigue in methamphetamine-abstained individuals was significantly reduced, and higher rate of fatigue recovery achieved, from daily administration of 100 mg amantadine for 4 weeks.